Two Models for Pollution, Part A, From Leviticus to Late Second Temple Literature - Meshel, Naphtali S. (Jewish studies quarterly, 2023)
Ancient Israelite and early Jewish texts on ritual purity vacillate between two incompatible conceptual models of pollution. According to the »disease« model, which is non-hierarchic, pollutions from diverse sources differ from one another qualitatively; according to the »temperature« model, pollutions are conceived as differing in degree. While no single text adheres to an unadulterated version of either model, this study demonstrates the explanatory power of a Two Model Theory for understanding biblical and early Jewish literature on pollution. Within Pentateuchal law, pollutions from different sources are nowhere hierarchized. This conception, which follows the disease model, was replaced in several late Second Temple texts by an alternative conception, wherein pollutions are mapped onto a hierarchy. A study of 4Q274 (4QTohorot A) and other late Second Temple texts demonstrates how this theoretical shift was achieved, how »severity« was invented and how the necessary terminology for the temperature model was »unearthed« from within Leviticus.